2006
DOI: 10.1097/01.rli.0000236921.77810.56
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Change Patterns of Microcomputed Tomography 3-Dimensional Bone Parameters as a High-Throughput Tool to Evaluate Antiosteoporotic Effects of Agents at an Early Stage of Ovariectomy-Induced Osteoporosis in Mice

Abstract: This study demonstrated the feasibility of evaluating the effect of the antiosteoporotic agents within 2 weeks after ovariectomy in mice. The muCT analysis may serve as a valuable tool, specifically in a high-throughput pharmacological screening test, offering useful information regarding the effects of test compounds on both bone resorption and formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
12
0
1
Order By: Relevance
“…20 Xiang et al reported that the trabecular bone volume, thickness, number, and connectivity of distal metaphyseal femur bones significantly decreased 2 weeks post-OVX in mice. 21 Our results also indicated statistical changes in the BV/TV of the L4 vertebral bone, suggesting the beginning of bone loss, in agreement with previous reports. In this study, the tendency toward bone loss was corrected only at 2 weeks after OVX with OA treatment, owing to the slight statistical significance exhibited by these indices between the sham and OVX rats.…”
Section: Discussionsupporting
confidence: 94%
“…20 Xiang et al reported that the trabecular bone volume, thickness, number, and connectivity of distal metaphyseal femur bones significantly decreased 2 weeks post-OVX in mice. 21 Our results also indicated statistical changes in the BV/TV of the L4 vertebral bone, suggesting the beginning of bone loss, in agreement with previous reports. In this study, the tendency toward bone loss was corrected only at 2 weeks after OVX with OA treatment, owing to the slight statistical significance exhibited by these indices between the sham and OVX rats.…”
Section: Discussionsupporting
confidence: 94%
“…In recent years, micro-computerized tomography (μCT) has been used to measure 3D bone structure of animals due to its relative ease in sample preparation, its noninvasive nature, and the high spatial resolution as compared with conventional histology [11]. Studies have demonstrated that μCT analysis of change patterns in 3D bone parameters may serve as a valuable tool for the evaluation of both anti-resorptive and anabolic agents in ovariectomized (OVX) animals [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies seen in the histomorphometry parameters between ovariectomized and sham-operated groups were surprising and it may be attributed to the small sample size used in our study. In addition, the technique used in measuring the histomorphometric parameters may not be sensitive since others have found that the use of high-throughput technique such as microcomputed tomography was able to yield more significant results [25]. …”
Section: Discussionmentioning
confidence: 99%